Analyzing the impact of the aspect ratio of a building on concrete use in its structure - Manish K. Dixit; Pranav Pradeep Kumar (Acta Polytechnica CTU Proceedings)
Buildings consume over half of annual energy supply as embodied and operating energy in their construction and operation releasing harmful emissions to the atmosphere. Over 90 % of the embodied energy is attributed to construction materials used in building structure, envelope, and interiors that must be reduced to minimize material use. Concrete is one of the major materials that contributes significantly to the energy and carbon footprint of buildings, as it is responsible for 5-9 % of global carbon emission. Because most of the concrete use in the building sector occurs in building structures, assessing how building design parameters influence its environmental sustainability is important. One of the design parameters that impact the sustainability of buildings is the aspect ratio, which is defined as the ratio of horizontal to vertical surface area of a building. A building with the same floor area can be designed horizontally or vertically with different aspect ratios, which will influence its structural design and eventually the amount of concrete used in the building. In this paper, we examine how aspect ratio may affect the environmental sustainability of a buildings foundation, structural framing, and slab. We model the structure of a generic building with different aspect ratio to analyze if aspect ratio can help reduce the energy and carbon embodied in reinforced concrete structures.